Ceting (Cegah Stunting) Bersama Remaja Putri Melalui Isi Piringku - Heryani, Heni; Lestari, Lusi; Suhanda, Suhanda (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2024)
One of the causes of stunting is due to inadequate nutrition during adolescence. One prevention that can be done is to approach the life cycle at the adolescent stage, especially adolescent girls as a preparation stage for prospective mothers from an early age. Young women must be prepared to enter the preconception period. These young women have a very big opportunity to break the chain of stunting. One intervention that can be carried out is providing education about balanced nutrition through the contents of my plate as early as possible to prevent stunting. The purpose of this community service is to increase knowledge about the contents of my plate. Carrying out service activities by providing education through giving ebooks about the contents of my plate to young women at SMPN 1 Ciamis. To measure the knowledge of young women with a pre-post test. The results of Community Service include an increase in young women's knowledge about the contents of my plate as a means of preventing stunting.